Trubadurski kult oblike kot jezikovnega ekvivalenta ljubezni - Novak, Boris A. (Primerjalna književnost, 1998)
The cult of form in the troubadour poetry as a language equivalent of love. - The treatise is based on the double analysis of the Old Provençal Troubadour poetry in the 12th and 13th century: on the one hand it follows the development of the poetic forms and genres, and on the other hand it tries to define the concept of the so called Court love on the basis of existent linguistic, historical, sociological and psychoanalitical analysis in order tofind out whether there is a correlation between the formal aspects of the Troubadour poetic language and the nature of their understanding of love. This research establishes that the basic drive of the Troubadour cult of the beloved Lady is longing; therefore, the conditio sine qua non for the Court love is that it cannot and should not be realized. Parallel with the process of the idealization of the Lady there is an increasing crystallization of the style movements (communicative trobar leu and hermetic trobar clus) and the differentiation of the poetic genres with the love song (canso) at its hierarchical peak with all the other genres submitted to it. The treatise pays a special attention to the different ways rhymes help link stanzas, and the dramatic development of different nets of rhymes which means the beginning and at the same time the peak of the art of rhymes in the European poetry. Considering the formal analysis of the poetic forms there are two possible interpretations of the origin of the Troubadour poetry: Christian liturgical form tropus / versus or the influence of the Arabian erotic poetry, especially the Mozarabic poetic form zéjel. On the different levels the analysis comes to the conclusion that there is identity between the art ofsinging and the art of loving and that the development of the formal procedures in the Troubadour poetry of the 12th and 13th century is parallel to the increasing idealization of the beloved Lady in the development of the concept of the Court love.
Keywords: francoska književnost; French literature; provansalska lirika; trubadurska lirika; ljubezenska lirika; verzologija; literarna teorija; literary theory